Magnetostrictive Actuation of a Bone Loading Composite for Accelerated Tissue Formation. (8th February 2012) - Hart, Stephen; Bucio, Ryan; Dapino, Marcelo
Abstract : When bone is dynamically loaded it adapts its shape to better support the load. We have developed a magnetostrictive composite consisting of Terfenol-D particles encapsulated in an epoxy resin that changes length when exposed to magnetic fields. When bonded to the surface of a porcine tibia ex vitro, the composite produces surface strains greater than 900  με at a frequency of 30 Hz and magnetic field of 170 kA/m. This is more than sufficient strain magnitude and frequency to promote cortical bone growth in both rats and turkeys and to maintain cortical bone structure in humans. Key advantages of the composite over conventional electromechanical or thermomechanical actuators are its simplicity, compact size, and remote actuation. A mathematical model describing the strains and stresses in the bone is presented.